Kesiapsiagaan Masyarakat dalam Menghadapi Bencana Kebakaran di Kampung Pelangi Kota Semarang Tahun 2020 - Cahyani, Yulia Fegy; Suharini, Erni (Edu Geography, 2021)
Kampung Pelangi is one of the populated areas in the city of Semarang. Populated areas are more risky fire disasters. This research aims to know the level of preparedness of Kampung Pelangi community, the level of preparedness of society according to education and to know the factors that inhibit community preparedness. This research was conducted in Kampung Pelangi Kota Semarang with sample 84 head of family. This research variable is preparedness with 5 parameters namely knowledge, Attitude, emergency response plan, early warning system, and resource mobilization. Results of the level of community preparedness showed that the 79 prepareness index was less prepared. These results were obtained from the knowledge parameter that got an index of 83 in the ready category, the attitude parameter got an index of 81 in the ready category, the parameters for emergency response plans got an index of 82 in the ready category, the parameters for the early warning system got an index of 76 in the less ready category, the parameters for resource mobilization got an index. 73 in the less ready category. Wilayah Kampung Pelangi merupakan salah satu kawasan padat penduduk di Kota Semarang. Kawasan padat penduduk lebih berisiko terjadi bencana kebakaran. Penelitian ini bertujuan untuk mengetahui tingkat kesiapsiagaan masyarakat Kampung Pelangi dan untuk mengetahui faktor-faktor yang menghambat kesiapsiagaan masyarakat. Penelitian ini dilakukan di Kampung Pelangi Kota Semarang dengan sampel 84 Kepala Keluarga. Variabel penelitian ini yaitu Kesiapsiagaan dengan 5 parameter yaitu pengetahuan, sikap, rencana tanggap darurat, sistem peringatan dini, dan mobilisasi sumber daya. Hasil tingkat kesiapsiagaan masyarakat menunjukkan indeks kesiapsiagaan 79 yang masukdalam kategori kurang siap. Hasil ini diperoleh dari parameter pengetahuan yang mendapat indeks 83 dengan kategori siap, parameter sikap mendapat indeks 81dengan kategori siap, parameter rencana tanggap darurat mendapat indeks 82 dengan kategori siap, parameter sistem peringatan dini mendapat indeks 76 dengan kategori kurang siap, parameter mobilisasi sumberdaya mendapat indeks 73 dengan kategori kurang siap.